Working together in a deficit logic: home–school partnerships with Somali diaspora parents. Issue 4 (4th July 2017) - Matthiesen, Noomi Christine Linde
Abstract: Drawing on discursive psychology this article examines the understandings teachers and principals in Danish Public Schools have regarding Somali diaspora parenting practices. Furthermore, the article investigates what these understandings mean in interaction with children in the classrooms and with parents in home–school communication. It is argued that in a society with increased focus on parental responsibility the teachers and principals draw on a deficit logic when dealing with Somali diaspora parents and children which consequently leads to teachers either transmitting their expertise by educating parents or compensating for perceived deficiencies in parental practices. Both these strategies result in significant marginalizing consequences where 'difference' is understood as 'wrong' or 'inadequate'.